Bilingual Language Intrusions and Other Speech Errors in Alzheimer’s Disease - Gollan, Tamar H. (Brain Cogn, 2017)
The current study investigated how Alzheimer’s disease (AD) affects production of speech errors in reading-aloud. Twelve Spanish-English bilinguals with AD and 19 matched controls read-aloud 8 paragraphs in four conditions (a) English-only, (b) Spanish-only, (c) English-mixed (mostly English with 6 Spanish words), and (d) Spanish-mixed (mostly Spanish with 6 English words). Reading elicited language intrusions (e.g., saying la instead of the), and several types of within-language errors (e.g., saying their instead of the). Patients produced more intrusions (and self-corrected less often) than controls, particularly when reading non-dominant language paragraphs with switches into the dominant language. Patients also produced more within-language errors than controls, but differences between groups for these were not consistently larger with dominant versus non-dominant language targets. These results illustrate the potential utility of speech errors for diagnosis of AD, suggest a variety of linguistic and executive control impairments in AD, and reveal multiple cognitive mechanisms needed to mix languages fluently. The observed pattern of deficits, and unique sensitivity of intrusions to AD in bilinguals, suggests intact ability to select a default language with contextual support, to rapidly translate and switch languages in production of connected speech, but impaired ability to monitor language membership while regulating inhibitory control.